Modeling the structural equations of the corona anxiety level based on psychological hardness and physical activities in the treatment staff of Ilam Province with the mediator role of professional identity - Shamseddin Rezaei; Morteza Shams; Akbar Azizifar; Sehat Aibod; Ziba Gohari (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The increase in deaths due to COVID-19 has increased anxiety among the treatment staff. Therefore, the purpose of this research was to model the structural equations of the anxiety level of corona based on psychological hardness and physical activities in the treatment staff of Ilam province with the mediator role of professional identity. MATERIALS AND METHODS: Based on the purpose, the method of this research is applied and based on how to obtain the data it is descriptive-correlational. The statistical population of the research includes all the treatment staff of Ilam province, with the number of 1900 people who were selected using Morgan's table, 320 people with the stratified sampling method as the sample. To collect the data, four standard questionnaires were used: Alipour et al. (2020) coronavirus anxiety questionnaire, Kiamarsi et al. (1998) psychological hardness, Baecke et al. (1982) physical activity, Hao et al. (2014) professional identity, and their validity and reliability were also confirmed. To analyze the data, from the indicators of descriptive statistics, Pearson's correlation coefficient test and structural equation model method (SEM) were used using SPSS and Amos software. RESULTS: The results of the research showed that psychological hardness, physical activities, and professional identity have a significant and inverse effect on the anxiety caused by corona, and the mediator role of professional identity in the relationship between physical activities and corona anxiety was confirmed, but this role was not confirmed in the relationship between psychological hardness and corona anxiety. CONCLUSION: To reduce the anxiety of the coronavirus in the treatment staff, the managers of the health and treatment centers of Ilam province should pay special attention to the employees' perceptions of psychological hardness, physical activities, and professional identity and provide them with the opportunity to create sports activities.